2014
DOI: 10.1111/boc.201300078
|View full text |Cite
|
Sign up to set email alerts
|

Dab1 and reelin participate in a common signal pathway that controls intestinal crypt/villus unit dynamics

Abstract: All together, the current findings link reelin with Dab1 and suggest that Dab1 functions downstream of reelin action on the homeostasis of the crypt-villus unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…The extracellular matrix protein Reelin has been found to promote the proliferation of intestinal and submandibular gland epithelial cells and granulose cells via ApoERs (VLDLR)/Dab1/PI3K/Akt and MAPK pathways303132. Whether similar function and similar signaling pathways can be found in Reelin-expressing tumors are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular matrix protein Reelin has been found to promote the proliferation of intestinal and submandibular gland epithelial cells and granulose cells via ApoERs (VLDLR)/Dab1/PI3K/Akt and MAPK pathways303132. Whether similar function and similar signaling pathways can be found in Reelin-expressing tumors are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Dab1 has been implicated in the regulation of cholesterol efflux in RAW 264.7 mouse macrophage cell line [24]. Vázquez-Carretero et al have reported that Dab1 participates in regulation of intestinal crypt/villus unit dynamics [25]. In addition, Dab1 is involved in regulation of mammary gland development, cartilage and tendon differentiation, odontogenesis, and granulosa cell proliferation in chicken follicle [2630].…”
Section: Discussionmentioning
confidence: 99%
“…Opto-Dab1 may also be useful to study Reelin-Dab1 signaling in synaptic plasticity140, in the development of non-neuronal tissues, such as mammary gland, small intestine and limbs, and in diseases including cancer414243. These applications will require the development of techniques to express opto-Dab1 effectively in the target cell types and to direct light to the respective tissues.…”
Section: Discussionmentioning
confidence: 99%